PENGARUH PENGETAHUAN PETUGAS CLEANING SERVICE TERHADAP PENGELOLAAN LIMBAH MEDIS PADAT DI RUMAH SAKIT BHAYANGKARA TK II SARTIKA ASIH BANDUNG - Lucy Rahmawati; Ai Susi Susanti (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study is to ascertain how expertise of cleaning service personnel affects the handling of solid medical waste at Bhayangkara Hospital TK II Sartika Asih Bandung. A quantitative research strategy with a descriptive focus was adopted. Techniques for gathering data, include distribution of surveys, observation, and literature review. Total population of 30 respondents. The sampling technique used saturated sampling technique with a total of 30 respondents. The data analysis technique used the Spearman rank correlation test and the T hypothesis test. The results of the study concluded that the effect of cleaning service staff knowledge on medical waste management used the Spearman rank correlation test of 81.9%, which means that it has a very close and positive relationship. Hypothesis T test results tcount 7.848 > ttable 2.052 and sign. 0.000 < 0,05. The study's finding is that the management of solid medical waste Rumah Sakit Bhayangkara TK II Sartika Asih Bandung is influenced by the expertise of cleaning service personnel.